KOMUNIKASI KELOMPOK RECURVE BEREGU PUTRI JAWA TIMUR PADA PEKAN OLAHRAGA NASIONAL XX - Teguh Dwi Putranto (Universitas Prof. Dr. Moestopo (Beragama), 2022)
Communication a necessary component of the training process that cannot be ignored until the competition period. Effective communication between fellow athletes during physical training, technical training, and mental training can lead to complete understanding for athletes. Likewise, during a match, when technical, physical, and mental exercise is no longer carried out before the match, communication cannot be ignored during the match. This study aims to determine how the group communication of the East Java women's team archery recurves at the XX National Sports Week (PON) in Papua. The East Java women's team recurve archery was chosen in this study because of the consistent achievement of East Java archery during participation in PON, one of which was in the women's team recurve number. The method used in this study is the semiotics of Charles Sanders Peirce in the final video of the East Java women's team archery competition at the Papua National Sports Week, which was obtained through the Youtube channel